-16h-1=20h+9

Simple and best practice solution for -16h-1=20h+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16h-1=20h+9 equation:


Simplifying
-16h + -1 = 20h + 9

Reorder the terms:
-1 + -16h = 20h + 9

Reorder the terms:
-1 + -16h = 9 + 20h

Solving
-1 + -16h = 9 + 20h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-20h' to each side of the equation.
-1 + -16h + -20h = 9 + 20h + -20h

Combine like terms: -16h + -20h = -36h
-1 + -36h = 9 + 20h + -20h

Combine like terms: 20h + -20h = 0
-1 + -36h = 9 + 0
-1 + -36h = 9

Add '1' to each side of the equation.
-1 + 1 + -36h = 9 + 1

Combine like terms: -1 + 1 = 0
0 + -36h = 9 + 1
-36h = 9 + 1

Combine like terms: 9 + 1 = 10
-36h = 10

Divide each side by '-36'.
h = -0.2777777778

Simplifying
h = -0.2777777778

See similar equations:

| 5x-60=2x+3+15 | | 11z+8=4z+11 | | -11f=7(1-2f+5) | | 6-3=5 | | 3y^3+2x^4y=7 | | -12g-9g-3=18 | | 2x^2+9x+41=0 | | x+y=4x-y+2 | | 5x-60=2x+3 | | w*4w=96 | | (5x+4)=16 | | v1/2=2 | | 6(x-1)-2x=3(x+1)+x | | 19w-10w-5=13 | | (2x+5)=(8x-5) | | 5(n-2)-3(2n+1)=4(1+n) | | 2x^2+5x-41=0 | | 20-14z=-20z-20+16 | | 2x^2+5-41=0 | | 15x/16=1/8 | | 15x/16 | | -18.53+11.6s-9.09=16.1s+6.58 | | -7c-5=-7c^2-3c+8 | | 7x+5y+1=0 | | -2(m-13)+-5=-9 | | 5*8(2*9)/4 | | -(8x+12)=(3x-(-13)) | | 3q-15=9+5q | | (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 |

Equations solver categories